Three new species of the extant genus Eucinetus from mid-Cretaceous amber of northern Myanmar (Coleoptera: Eucinetidae) - Li, Yan-Da; Engel, Michael S.; Huang, Di-Ying; Cai, Chen-Yang (Zootaxa, 2024)
Three new species of plate-thigh beetles are described and figured from mid-Cretaceous Kachin amber, all representing the extant genus Eucinetus Germar. The species, Eucinetus debilispinus Li & Cai sp. nov., E. panghongae Li & Cai sp. nov., and E. zhenhuai Li & Cai sp. nov., are distinguished from each other by the forms of the antennomeres, leg spination, and form of the spurs. The genus Eucinetus represents a key example of long-term evolutionary stasis with a subcortical lifestyle. This further demonstrates the role of stable cryptic microhabitats in the persistence of some lineages over vast spans of geological time.